Evaluation of performance of irrigation canals using benchmarking techniques –a case study of Hirakud dam canal system, Odisha, India. Issue 1 (2nd January 2020) - Rath, Ashutosh; Swain, Prakash Chandra
Abstract: The main motto behind the performance assessment of an irrigation system is to utilize the available water resources in an efficient and effective manner. In recent times there has been a growing concern that performance in the context of irrigated agriculture is less than that had been anticipated. Deficit water supply results in loss of production, while excess water delivery leads to waterlogging and salinity. Water supply at any given location is often poorly matched to crop need and is highly variable in both time and discharge. Good performance is not only a matter of high output, but also one of efficient use of available resources. In the present study, evaluating the performance of a canal system was conducted in two parts of Hirakud canal system namely Paramanpur distributary and Senhapali distributary. The flow measurement was done using flow tracker ADV, an instrument which measures the flow with relatively more accuracy. Various indicators of performance in a flow irrigation system, such as adequacy, variability, efficiency, inequity, conveyance performance,  and irrigation performance were used to evaluate the performance of the canals. The evaluation indicates that more attention should be given for the canal operation strategy to get optimal output from the system.